Increasing Charge While Preserving Noncovalent Protein Complexes for ESI-MS - Lomeli, Shirley H. (2008)
Increased multiple charging of native proteins and noncovalent protein complexes is observed in electrospray ionization (ESI) mass spectra obtained from nondenaturing protein solutions containing up to 1% (v/v) m-nitrobenzyl alcohol (m-NBA). The increases in charge ranged from 8% for the 690 kDa α(7)β(7)β(7)α(7) 20S proteasome complex to 48% additional charge for the zinc-bound 29 kDa carbonic anhydrase-II protein. No dissociation of the noncovalently bound ligands/subunits was observed upon the addition of m-NBA. It is not clear if the enhanced charging is related to altered surface tension as proposed in the “supercharging” model of Iavarone and Williams (Iavarone, A. T.; Williams, E. R. J. Am. Chem. Soc. 2003, 125, 2319–2327). However, more highly charged noncovalent protein complexes have utility in relaxing slightly the mass-to-charge (m/z) requirements of the mass spectrometer for detection and will be effective for enhancing the efficiency for tandem mass spectrometry studies of protein complexes.